Chest trauma management; An experience at trauma center, postgraduate medical institute, Quetta - Muhammad Arif Khan; Muhammad Iqbal Khan; Riffat Arbab; Abdullah Khan; Maria Mahmood; Nazia Naseer (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVE: Chest trauma is a leading cause of global morbidity and mortality, especially among young adults. The rising incidence in Pakistan underscores the need for local research to inform effective management. The objective of the current study is to determine the variety of chest trauma and its associated factors among patients admitted to the Trauma Centre, Postgraduate Medical Institute (PGMI), Quetta.METHODOLOGY: A  cross-sectional quantitative study was conducted at Trauma Centre PGMI Quetta from March 1, 2024, to August 31, 2024, after obtaining ethical approval (PGMIQ/ERC/16/2024). We reviewed 200 chest trauma patients, admitted to the surgical unit of the trauma centre and analyzed the data. Fisher tests analyzed  the relationship between management approaches and patient status upon arrival, as well as thoracotomy findings and initial management approaches.RESULTS: Of the 200 patients, 167 (83.5%) were male, and 33 (16.5%) were female. Most (69.5%) had injuries from road traffic accidents or falls. Rib fractures occurred in 75 (37.5%) patients, with 40 (20%) on the left side and 35 (17.5%) on the right. Fisher’s Exact test revealed significant associations between management approach and patient arrival status (p = 0.013) and between management approach and thoracotomy findings (p = 0.000), respectively.CONCLUSION:  Chest trauma is a significant health concern, particularly among young males, often caused by road accidents and falls. While most cases involve blunt trauma and can be managed conservatively, thoracotomy is typically required for hemothorax cases with vascular or pulmonary injuries.